A naphthalimide-linked new pyridylazo phenol derivative for selective sensing of cyanide ions (CN−) in sol–gel medium. Issue 5 (22nd January 2021) - Ghosh, Sumit; Jana, Palash; Ghosh, Kumaresh
Abstract : Napthalimide-linked pyridylazo derivatives 1 and 2 are designed and synthesized. While compound 1 acts as a gelator in DMF–H2 O (1 : 1, v/v), compound 2 does not show gelation under the conditions. Compound 1 selectively senses CN – in sol-gel medium. Abstract : Napthalimide-linked pyridylazo derivatives 1 and 2 have been designed and synthesized. Compound 1 acts as a gelator in DMF–H2 O (1 : 1, v/v). The brown gel is photostable and shows good viscoelastic properties. The value of G ′ is almost 10 times higher than that of G ′′ over the entire range of frequencies at a constant strain of 1%. The SEM image shows the presence of densely stacked flakes. In comparison, compound 2, devoid of free phenolic –OH, does not show gelation properties under identical conditions. However, the brown gel of 1 shows selective sensing of CN − ions over a series of anions involving phase change through the deprotonation mechanism. While the brown gel of 1 is selectively ruptured in the presence of CN − to the sol, compound 1 in solution shows measurable UV-vis and emission changes in the presence of CN − over the other anions and validates the visual sensing of CN − . In the test-kit application, the yellow paper strip turned into pinkish-red upon contact with CN − .